A Survey of Recent Patents in Engineering Technology for the Screening, Separation and Processing of Eggshell - Ahmed, Tamer A. E.; Younes, Manar; Wu, Ling; Hincke, Maxwell T. (Frontiers in Bioengineering and Biotechnology, 2021)
The chicken egg is a well-known complete food of human daily consumption which serves as a cost-effective, high-quality nutrient resource. About 30% of table eggs are directed to breaker plants in developed countries, leading to the generation of substantial eggshell (ES) waste, which is increasingly explored for potential value-added applications. The number of patents describing ES-based applications has increased dramatically in recent years. This review provides insight into the most recent patents published between 2015 and 2020, with focus on different engineering technologies for the screening, separation, and processing of ES. Screening technologies include detection of ES surface spots and glossiness, ES cracks, and mechanical properties, along with identification of chicken breed and enumeration of surface bacterial count. Collection and separation technologies describe separation strategies of ES from egg white (EW), egg yolk (EY), liquid egg, eggshell membrane (ESM), hatchlings, and cooked egg. Separation of ES from liquid eggs utilizes gravity, rotational forces, or air pressure. Processing of ES involves washing and sterilization along with cutting, crushing, and pulverization technologies that enable the collection of ES suitable for value-added applications. In addition, ES carving (mechanical and laser) opens up the realm of artwork and decoration. Furthermore, intact ES can be utilized for food serving. The exponential increase in innovative screening, separation, collection, and processing technologies reflects industrial interest to upscale low-value ES waste material, and is a first crucial step in the emergence of advanced technologies that exploit the biomedical, chemical, engineering, and environmental applications for ES.